Manipulating the symmetry of photon-dressed electronic states - Changhua Bao; Michael Schüler; Teng Xiao; Fei Wang; Haoyuan Zhong; Tianyun Lin; Xuanxi Cai; Tianshuang Sheng; Xiao Tang; Hongyun Zhang; Pu Yu; Zhiyuan Sun; et al. (Nature Communications, 2024)
Abstract Strong light-matter interaction provides opportunities for tailoring the physical properties of quantum materials on the ultrafast timescale by forming photon-dressed electronic states, i.e., Floquet-Bloch states. While the light field can in principle imprint its symmetry properties onto the photon-dressed electronic states, so far, how to experimentally detect and further engineer the symmetry of photon-dressed electronic states remains elusive. Here by utilizing time- and angle-resolved photoemission spectroscopy (TrARPES) with polarization-dependent study, we directly visualize the parity symmetry of Floquet-Bloch states in black phosphorus. The photon-dressed sideband exhibits opposite photoemission intensity to the valence band at the Γ point, suggesting a switch of the parity induced by the light field. Moreover, a “hot spot” with strong intensity confined near Γ is observed, indicating a momentum-dependent modulation beyond the parity switch. Combining with theoretical calculations, we reveal the light-induced engineering of the wave function of the Floquet-Bloch states as a result of the hybridization between the conduction and valence bands with opposite parities, and show that the “hot spot” is intrinsically dictated by the symmetry properties of black phosphorus. Our work suggests TrARPES as a direct probe for the parity of the photon-dressed electronic states with energy- and momentum-resolved information, providing an example for engineering the wave function and symmetry of such photon-dressed electronic states via Floquet engineering.